1996
DOI: 10.1159/000217296
|View full text |Cite
|
Sign up to set email alerts
|

Influence Of Hypoxia And Hypoxia-Reoxygenation On Endothelial P-Selectin Expression

Abstract: P-selectin is an endothelial adhesion molecule involved in the initial step of the neutrophil recruitment. We investigated the effect of hypoxia (95% N2, 5% CO2) and of hypoxia-reoxygenation (95% air, 5% CO2) on the expression of P-selectin by human umbilical vein endothelial cells (HUVEC). P-selectin expression was detected by immunolabelling and quantified by flow cytometric analysis. Our data indicate that hypoxia induces an increase in P-selectin expression with a maximum r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…It has been demonstrated that discrete cell-surface markers (ie, ␣ v ␤ 3 and E-selectin) are up-regulated in endothelial cells exposed to severe hypoxia. [51][52][53] These or similarly functioning molecules are potential candidates for the selective homing of EPCs to ischemic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that discrete cell-surface markers (ie, ␣ v ␤ 3 and E-selectin) are up-regulated in endothelial cells exposed to severe hypoxia. [51][52][53] These or similarly functioning molecules are potential candidates for the selective homing of EPCs to ischemic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we confirmed the observation that a relatively brief period of hypoxia followed by reoxygenation elicits a significant increase in P-selectin at the endothelial surface of saphenous vein. 35 However, vein segments from a patient under statin treatment expressed significantly less P-selectin on the endothelial surface after 50 minutes of hypoxia followed by reperfusion, with a beneficial effect on leucocyteendothelial interactions compared with controls. This effect was not related to the cholesterol lowering effect of simvastatin, as it was also manifested in group B patients who did not benefit from simvastatin treatment in terms of reduced cholesterol.…”
Section: Modulation Of Neutrophil-endothelial Interactions By Statinsmentioning
confidence: 90%
“…In addition to modulating the pro and anticoagulant properties of the endothelium, hypoxia also up regulates the expression of P-selectin on endothelium leading to the recruitment of leukocytes or leukocyte microparticles containing tissue factor which can serve as the nidus for initiation of the thrombotic response 18,19 (Figure 2). Microparticles bearing tissue factor appear to play a role in thrombus formation 20,21 .…”
Section: A the Role Of Blood Cells Versus Vascular Contribution To Vmentioning
confidence: 99%